Implementation of a Web-Based Daily Worker Recruitment Application Using the CodeIgniter 3 Framework at PT Artha Kreasi Utama - Upay Sutisna (SAN Scientific, 2025)
The rapid development of information technology has encouraged companies to innovate in human resource management, including recruitment processes. PT Artha Kreasi Utama, an outsourcing company that supplies labor for Lazada warehouses, faces challenges in managing the recruitment of daily workers, which is still carried out manually. This manual process results in slow administration, difficulty in tracking applicant status, and subjectivity in candidate selection. This study aims to develop a web-based recruitment information system using the CodeIgniter 3 framework to manage applicant data more efficiently. The system also implements the Multi-Factor Evaluation Process (MFEP) method to assess candidates objectively based on predetermined criteria. The development method used is Extreme Programming (XP), which allows the application to be developed quickly and flexibly according to continuously evolving needs. With the system that has been developed, the recruitment process becomes more structured, transparent, and efficient. Applicant data management is more organized, candidate assessment is more objective, and tracking and reporting of applicant status can be done in real-time. As a result, the company can obtain daily workers who meet Lazada's warehouse operational needs more quickly and accurately.